Interaction of caffeic acid with SDS micellar aggregates - Cid, Antonio (2022)
co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007728). Associate Laboratory for Green Chemistry-LAQV, which is financed by national funds from FCT/MCTES (UID/QUI/50006/2019). This work received financial support from Programa de Cooperacion Interreg V-A Espana-Portugal (POCTEP) 2014-2020 (project Ref: 0377_IBERPHENOL_6_E).